Impact of Smoking History on Response to Immunotherapy in Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Zhao, Wenhua; Jiang, Wei; Wang, Huilin; He, Jianbo; Su, Cuiyun; Yu, Qitao (Frontiers in Oncology, 2021)
Objectives: To evaluate the impact of smoking history on the clinical benefit of immunotherapy in patients with non-small cell lung cancer (NSCLC). Methods: Twenty-three randomized clinical trials and seven real-world studies were included in this meta-analysis. Hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) and progression-free survival (PFS) and odds ratios for the overall response rate (ORR) were extracted. A fixed-effects or random-effects model was applied to obtain pooled estimates. Results: Data from 16 high-quality trials involving 10,643 NSCLC patients receiving either immunotherapy or chemotherapy/placebo enabled direct comparison of the survival impact of smoking. Anti-PD-1/PD-L1/CTLA-4 immunotherapy was found to significantly prolong OS and PFS as compared to chemotherapy/placebo in smokers (HR for OS, 0.76 [0.69–0.83], P<0.00001; HR for PFS, 0.65 [0.56–0.75], P<0.00001), and these trends were less or not significant in non-smokers (HR for OS, 0.91 [0.78–1.06], P=0.25; HR for PFS, 0.68 [0.45–1.03], P=0.07). Consistent results were obtained for the first-line or second/third-line use of immunotherapy and for non-squamous NSCLC patients only. Furthermore, the data from 7 trials and 7 real-world studies involving 4,777 patients receiving immunotherapy allowed direct comparison of therapeutic outcomes between smokers and non-smokers. Prolonged OS (HR 0.86 [0.75–0.99], P=0.04) and PFS (HR 0.69 [0.60–0.81], P<0.0001) and a higher response rate (ORR 1.20 [0.94–1.53], P=0.15) were observed in smokers compared to non-smokers receiving immunotherapy. Conclusions: Immunotherapy was found to have a greater benefit in NSCLC patients with a smoking history than in those who had never smoked.